PENGARUH PENGETAHUAN, SOSIALISASI DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK UMKM PASAR DESA PENGALANGAN - Ronaldus Roi Sandoko; Heru Tjahjono (Jurnal Ekonomi, Bisnis dan Social, 2024)
The aim of this research is to examine whether Tax Knowledge, Tax Socialization, and Tax Sanctions influence the Compliance of SME Taxpayers in the Pengalangan Village Market. This study utilizes a quantitative method to investigate the impact of Tax Knowledge, Tax Socialization, and Tax Sanctions on Taxpayer Compliance in the Pengalangan Village Market. The sample consists of 108 respondents from SMEs, selected intentionally. Data is collected through questionnaires, interviews, and documentation. The validity and reliability of the questionnaire are tested to ensure the questions are appropriate and consistent. Data analysis employs basic statistical tests, and hypotheses are tested using a multiple linear regression model, evaluating the influence of each variable and their combination on Taxpayer Compliance. The results of this study indicate that Tax Knowledge, Tax Socialization, and Tax Sanctions significantly influence the Compliance of SME Taxpayers in the Pengalangan Village Market.